A STUDY OF RELATIONSHIP BETWEEN TEACHERS’ PERCEPTIONS TOWARDS PRINCIPAL’S INSTRUCTIONAL LEADERSHIP STYLE AND THEIR COMPETENCE AT THE SCHOOL OF MUNGMYIT SINLI IDPS HIGH SCHOOL, KACHIN STATE, MYANMAR - JA SAN MAI, HPAUYU; YE, YAN (Scholar: Human Sciences, 2022)
The study analyzed the teachers’ perceptions towards the principal’s instructional leadership style and teachers’ competence at the Mungmyit Sinli IDPs High School, Kachin State, Myanmar. It was to identify the relationship between the teachers’ perceptions of the principal’s instructional leadership style and their competence at the Mungmyit Sinli IDPs High School during the academic year of 2020. The population for this study was 58 full-time teachers working at Mungmyit Sinli IDPs High school. For data collection, the researcher used two research instruments. Part one: the questionnaires on the five functions of a principal’s instructional leadership (Krug, 1992) were adopted from Jerman (2001), and Part two: the five components of teachers’ competence (Medley, 1977) was adopted from Kavinda (2014). In order to test the hypothesis of this study, the collected data were statistically analyzed by the Pearson Product Moment Correlation. It was found that there was a strong and positive relationship between the teachers’ perceptions of the principal’s instructional leadership style and their competence at the Mungmyit Sinli IDPs High School. This study revealed that enhancing teachers’ knowledge, abilities, and skills development could be helped by principal frequent formative evaluation, observation, and interaction with each teacher of instruction practice processes in the classroom. Hence, it was recommended that the principal should emphasize joining an informal discussion with teachers in their teaching with teaching skills and knowledge such as pedagogies and educational theories. In addition, the teachers and principal should be in continuing professional development such as training programs, workshop programs, and other Computer technology programs to assist their competence development.